1984
DOI: 10.1111/j.1471-4159.1984.tb12781.x
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of Myelin Basic Protein by Neutral Protease Activity of Human White Matter and Myelin

Abstract: Polypeptides arising from neutral in vitro proteolysis of myelin basic protein (MBP) of human brain were evaluated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. At pH 7 a marked breakdown of MBP resulted in the formation of 8-12 polypeptides ranging from 6 to 17 kd in molecular weight. As neutral proteolytic activity was not eliminated by either gel filtration or cation-exchange chromatography acid-soluble protease(s) involved probably have a size and electric charge similar to that of MBP. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…When CNS myelin is partially or completely ablated, damaged axons in the vicinity are capable of extensive neurite outgrowth (Dyer et al, 1998;Keirstead et al, 1995Keirstead et al, , 1998Keirstead et al, , 1999. Several lines of evidence suggest that myelin has endogenous protease activity with the potential to degrade myelin proteins (Berlet et al, 1984;Chantry et al, 1989;Sato et al, 1982). An in vitro biochemical assay showed that neuropsin degraded myelin basic protein (He et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…When CNS myelin is partially or completely ablated, damaged axons in the vicinity are capable of extensive neurite outgrowth (Dyer et al, 1998;Keirstead et al, 1995Keirstead et al, , 1998Keirstead et al, , 1999. Several lines of evidence suggest that myelin has endogenous protease activity with the potential to degrade myelin proteins (Berlet et al, 1984;Chantry et al, 1989;Sato et al, 1982). An in vitro biochemical assay showed that neuropsin degraded myelin basic protein (He et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
“…Within unlesioned spinal cord white matter, a subpopulation of mature oligodendrocytes and oligodendrocyte progenitors expressed protease M/neurosin. These cells may function in normal homeostasis such as turnover of the myelin sheath (Berlet et al, 1984). After injury to the spinal cord, some of the protease M/neurosin-expressing cells also expressed neuropsin and most of the cells expressing neuropsin were CNPase-positive oligodendrocytes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been suggested that oligodendrocytes and myelin have endogenous protease activity with the potential to degrade myelin proteins (Sato et al, 1982;Berlet et al, 1984;Chantry et al, 1989;Scarisbrick et al, 2002;Terayama et al, 2005b). The in vitro biochemical assay showed that neuropsin is capable of degrading MBP (He et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Since oligodendrocytes have protease activity which might contribute to the pathology after SCI (Berlet et al, 1984), the identification and characterization of key enzymatic players may suggest new therapeutic targets to reduce further damage and promote remyelination. Kallikreins are serine proteases that comprise a recently -6 -identified large and closely related 15-member family in humans.…”
Section: Introductionmentioning
confidence: 99%